Korean in a Flash Volume 2. - Soohee (Tuttle Publishing, 2014)
Korean in a Flash Volume 2 continues the learning-tool advantage for people interested in learning Korean quickly and easily. This complete boxed set of flash cards has a full range of acclaimed features to help beginners and intermediate learners, and covers the second most-basic Korean words, plus related terms and phrases-in a flash! Contains 448 flash cards plus a 48 page index booklet. Learn 448 main words plus 1,792 related terms and 2,240 basic vocabulary items. Romanized pronunciation and English meanings given for all vocabulary items. Both Korean character forms and romanization are given.